47.2k views
1 vote
What is the rule for the reflection?

A. ry=x(x, y) → (–y, –x)
B. ry=–x(x, y) → (–y, –x)
C. ry=x(x, y) → (y, x)
D. ry=–x(x, y) → (y, x)

What is the rule for the reflection? A. ry=x(x, y) → (–y, –x) B. ry=–x(x, y) → (–y-example-1
User Dbajgoric
by
4.7k points

2 Answers

3 votes

Answer:

Your answer would be letter C.

Explanation:

Took the quiz and got it right on edge2020

User RomualdM
by
6.5k points
3 votes

Answer:

C. r y = x (x, y) → (y, x).

Explanation:

It appears that the triangle was reflected over the line y = x. According to the Coordinate Rules of Reflection, (x, y) would change and become (y, x). That resembles option C. r y = x (x, y) --> (y, x).

Hope this helps!

What is the rule for the reflection? A. ry=x(x, y) → (–y, –x) B. ry=–x(x, y) → (–y-example-1
User Andrin
by
6.2k points